SALES GROWTH, LIQUIDITY, LEVERAGE AND FINANCIAL DISTRESS: TESTING THE INTERACTION EFFECT OF PROFITABILITY - Muhamad Dafa Ilhani Salim; Rizky Fauzan; Wendy Wendy; Mustarudin Mustarudin; Uray Ndaru Mustika (SEAN Institute, 2023)
Financial Distress is an important issue and requires deep attention, especially in the Consumer Goods Industry with high competition. This quantitative research aims to test the impact of Sales Growth, Liquidity, and Leverage on Financial Distress with Profitability as moderation. The research data was collected from companies listed on the Indonesian Stock Exchange (IDX) and then tested using logistical regression analysis techniques. Research results show that Leverage influences Financial Distress. In addition, Profitability can also moderate the influence of Liquidity and Leverage on Financial Distress. Other findings suggest that Sales Growth and Liquidity do not affect Financial Distress when tested in person. Thus, this research confirms the role of Profitability as moderation.